A second wind for wiring [ADSL]. - Dutta-Roy, A. (IEEE spectrum)
Asymmetric digital subscriber line (ADSL) modems deliver voice and high-speed data (at up to 6 Mb/s) simultaneously over ordinary twisted pairs. The author discusses the technology involved and its implementation. Various aspects of the service are considered together with Internet access